An Analysis of Educational Values of Novel “Maze Runner” by James Dashner - Ramba Irawan; Dwi Andriani (Channing : Journal of English Language Education and Literature, 2018)
In this study, the writer conducted "Maze Runner" novel, it educated the values as a part of our life. The problems were what are the educational values seen in the novel "Maze Runner" by James Dashner. The methodology of the study was qualitative study, it did not need statistic approach to explore the material, the descriptive analyzes. The primary data was from "Maze Runner" novel. The secondary data was from many literary books and some relevant materials to support and complete the primary data sources. The result of the research was there were some educational values in the "Maze Runner" novel found, it was never given up, self-confidence, friendly and be polite, love, forgiveness, optimism, help each other and responsible as a human society. And the most occurred was never give up and optimism.